To fetch a thief [compact disc, unabridged] - Quinn, Spencer (Quinn, Spencer. Chet and Bernie mystery., 2010)
When the traveling circus comes to down and its star attraction and his trainer go missing, P.I. Bernie Little and his companion Chet are on the case. Hired by Popo the Clown, Bernie and Chet discover that there are some dangerous people behind the disappearances, people who will go at any length to make the sleuthing duo disappear, too.